PENERAPAN TPM DENGAN MENGGUNAKAN OVERALL EQUIPMENT EFECTIVENESS (OEE) DAN SIX BIG LOSSES PADA MESIN REVERSE OSMOSIS DI BAGIAN UTILITY PT. WIDATRA BHAKTI - Eko, Andi; Hermansyah, Muhammad (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
Manufacturing system improvement is one of the intensive improvements made so that later it can resp ond to market changes quickly. The company is always trying to increase productivity, one way to do that is by implementing a preventive and corrective maintenance system. However, in reality the results achieved were not in line with expectations. This study found that the amount of time taken to carry out maintenance breakdowns, which is one of the real problems, so corrective action was focused on this problem. In this study using OEE measurement methods, analysis of the calculation of Six Big Losses, and analysis of cause and effect diagrams to find out the problems that occur and provide suggestions for solving the problem. From the analysis and discussion that has been carried out, several results are obtained, namely the OEE value in the Reverse Osmosis machine is between 38.2% - 45.3% and is below the OEE standard (85%). The low OEE value is strongly influenced by the low availability rate which only ranges between 62.5% - 83.3% and is far below the standard availability rate (90%). The results of this study found that the biggest factors that influence the low effectiveness of the engine are the reduced speed factor of 30.31% and the scrap loss yield of 53.37%. so the recommended action is the application of TPM.